Papaya cures chickens - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Researchers at the University of Dschang in Cameroon have discovered that diluted papaya seeds can be used to treat chickens suffering from infestations of gastrointestinal parasites like Heterakis sp. and Eimeria sp. Seeds were dried in the sun for...